2022
DOI: 10.1371/journal.pone.0277647
|View full text |Cite
|
Sign up to set email alerts
|

Investigating impacts of small dams and dam removal on dissolved oxygen in streams

Abstract: Small surface-release dams are prevalent across North American watersheds and can alter stream flow, thermal regimes, nutrient dynamics, and sediment transport. These dams are often implicated as a cause of negative water quality impacts—including reduced dissolved oxygen (DO)—and dam removal is increasingly employed to restore natural stream processes and improve DO. Published impacts of small dams on DO vary widely across sites, and even less is known about the extent and timescale of DO recovery following r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Velinsky et al (2006) observed no significant effects of a small dam on Manatawny Creek (United States) or its removal on the concentrations and forms of carbon (C), N or P; they concluded that the residence times were too short and the thermal stratification too weak to influence nutrient cycling. Abbott et al (2022) monitored dissolved oxygen concentration continuously for 3 weeks in summer at 15 river sites in the United States before and after removal of their small dams; they found that the reservoir's oxygen signal returned to the upstream reference at 80% of sites within 1 year of the removal. Riggsbee et al (2012) used experiments to quantify nutrient fluxes before and after removal of a dam on the Little River (United States) and identified that vegetation had a significant influence on N and P leaching during the first growing season after removal and that it likely would have a larger influence in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…Velinsky et al (2006) observed no significant effects of a small dam on Manatawny Creek (United States) or its removal on the concentrations and forms of carbon (C), N or P; they concluded that the residence times were too short and the thermal stratification too weak to influence nutrient cycling. Abbott et al (2022) monitored dissolved oxygen concentration continuously for 3 weeks in summer at 15 river sites in the United States before and after removal of their small dams; they found that the reservoir's oxygen signal returned to the upstream reference at 80% of sites within 1 year of the removal. Riggsbee et al (2012) used experiments to quantify nutrient fluxes before and after removal of a dam on the Little River (United States) and identified that vegetation had a significant influence on N and P leaching during the first growing season after removal and that it likely would have a larger influence in the long term.…”
Section: Introductionmentioning
confidence: 99%